The personalized sport trainning in its periods - Vladimir Medina Vaillant (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
The sport training is a process that, by means of the physical exercise, tends to reach a more or less high level according to the proposed objectives, causing a modification of the physical, motor, cognitive and affective state on the athletes with the aim to obtain competitive results. It can also be defined as the main form of putting into practice the sportsman's preparation, being the most important features the fact that it represents an organized didactic process which is characterized by the rigorous use of all teaching, education and selfeducacion process factors, as well as a methodological system of the physical exercises that constitutes the base of the sport training with the purpose of achieving the biggest effect in the development, whenever it is possible to direct the process of sport improvement fully. The personality is a concrete person in all his/her social and psychological particularities diversity; it is the subject of the social activity and of the social relationships. One of the most characteristic aspects in the human personality is his/her individuality, understanding it as a group, only in his/her gender, with psychological particularities that makes each individual different from the other ones, in relation with the character, the temperament, the peculiarities to reflect the psychic processes, the group of feelings and reasons for the activity. The understanding and the consideration of the individual particularities have a great importance in the sportsman's practical life during the training. Starting from the inadequacies detected in the trainings and competitions connected with the athletes' preparation, assimilation and application of the received knowledge, we propose the present material about personalized training, like tool for trainers´ development in order to achieve the sportsman's more complete preparation, taking into account the contemporary training direction. There were used investigative methods, as: the observation, interview and work with documents, among other ones.